Kemitraan Multi Pihak Dalam Penanggulangan Kemiskinan (Studi Kasus Program Gandeng Gendong Kota Yogyakarta) - Linda, Rusna Eva; Hadiwijoyo, Suryo Sakti; ., Daru Purnomo (Department of Public Administration, Muhammadiyah University of Makassar, 2024)
Gandeng Gendong Program is a program to solve the issue of poverty in the city of Yogyakarta. In the implementation of activities, the governance structure of the Gandeng Gendong program involves 5K which consists of the Village (Yogyakarta City Residents), Campus (Tridarma), Yogyakarta City Government, Corporate (private), and Community. The purpose of research is to analyze Multi-Party partnerships and the implementation of the Gandeng Gendong program in poverty reduction in the city of Yogyakarta. This research uses a descriptive qualitative method. The results of this study show that in Giddens' structural theory, the relationship between